Evaluation Of the UKT Payment Relaxation Policy at Gorontalo State University - Usulu, Wahidun; Igirisa, Irawaty (Abdurrauf Science and Society, 2025)
Higher education is a constitutional right of every citizen and a strategic means of developing superior human resources. To ensure equitable access to higher education, the government has implemented a Single Tuition Fee (UKT) policy as a financing scheme tailored to students' economic capabilities. However, in practice, the implementation of the UKT payment relaxation policy at Gorontalo State University has not fully reflected the principles of social justice and the effectiveness of public policy. This study aims to evaluate the implementation of the UKT relaxation policy through a qualitative descriptive approach and using the Alkin evaluation model (UCLA Model) which includes five components: system assessment, program planning, implementation, improvement, and benefits. Data collection techniques were carried out through observation, interviews, and documentation, with data analysis using the Miles and Huberman interactive model. The results of the study indicate that the UKT relaxation policy has not been well-targeted, because it is not supported by a valid student economic database and does not involve a participatory evaluation process. Furthermore, the policy verification and oversight system is still weak, making it vulnerable to abuse by students from middle- to upper-class families. The implications of these findings point to the need for policy reformulation based on accurate data, transparent governance, and increased institutional capacity to realize inclusive and equitable access to higher education